W H Smith improves indie access. - Bone, Alison (Bookseller, 2005)
The article reports that small publishers struggling to sell to retail chains have welcomed a move by WH Smith (WHS) to improve access to buyers. The move was revealed at an evening with retail buyers, organized by the Independent Publishers Guild. WH Smith's independent publishers scheme, which it has been developing since the end of last year, runs in conjunction with Gardners Books. The wholesaler whittles down the 500-plus books presented by independent publishers every two months and comes up with the top 70 to 100, which it shows to WHS. The retailer then makes a decision on which to take on.